2015
DOI: 10.1128/mcb.00024-15
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Cdk7 Controls Gene Expression through both Its CAK and C-Terminal Domain Kinase Activities

Abstract: Cyclin-dependent kinases (Cdk) coordinate timely progression through the cell cycle. Cdk activity is modulated by the association of regulatory subunits (cyclins, inhibitors, and assembly factors) and by activating and inhibiting phosphorylation at conserved residues (1). Phosphorylation within the activating segment, referred to as the T loop, is essential for maximal activity and is catalyzed by a Cdk-activating kinase (CAK) (2, 3). Genetic and biochemical studies in several model organisms pointed to Cdk7-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Our recent work identified RSC as a key downstream effector of a cascade controlling the level of acetylation around the NDR of ste11 , which encodes the master regulator of gametogenesis in S. pombe (Anandhakumar et al 2013; Cassart et al 2012; Coudreuse et al 2010; Devos et al 2015). Deletion of non-essential subunits of RSC or transcriptional switch-off of snf21 both impede ste11 expression and correlate with higher nucleosome occupancy at the ste11 NDR (Materne et al 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work identified RSC as a key downstream effector of a cascade controlling the level of acetylation around the NDR of ste11 , which encodes the master regulator of gametogenesis in S. pombe (Anandhakumar et al 2013; Cassart et al 2012; Coudreuse et al 2010; Devos et al 2015). Deletion of non-essential subunits of RSC or transcriptional switch-off of snf21 both impede ste11 expression and correlate with higher nucleosome occupancy at the ste11 NDR (Materne et al 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite discrepancies, genome-wide analyses of CTD phosphorylation support that the CTD cycle is uniform across genes ( Kim et al, 2010 ; Mayer et al, 2010 ; Tietjen et al, 2010 ; Bataille et al, 2012 ), and a broad body of evidence supports the seminal role of CTD S5P and S2P in transcriptional regulation and chromatin metabolism ( Buratowski, 2009 ). However, recent works showed that contrary to S5P, S2P is dispensable in both fission yeast and budding yeast ( Cassart et al, 2012 ; Devos et al, 2015 ) and only affects the steady-state level of a subset of mRNAs ( Coudreuse et al, 2010 ; Saberianfar et al, 2011 ; Sukegawa et al, 2011 ). Therefore, a disconnect exists between the apparent uniform occupancy of the phosphorylated PolII and the gene-specific defects resulting from the disappearance of a phosphorylation; a similar case occurring with chromatin regulators ( Drogat and Hermand, 2012 ; Egloff et al, 2012 ; Weiner et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…When unbound of TFIIH, TFIIK plays a pivotal role in cell cycle control through activation of cell cycle kinases by T‐loop phosphorylation. Cell cycle kinase‐activating kinase (CAK) activity of human CDK7 is mediated by autophosphorylation and CYCH binding (Martinez et al ., ; Fisher, , ), whereas for binding of Msc2/cyclin H Msc6 requires its T‐loop phosphorylation by the Csk1 CAK‐kinase (CAKAK), which has no CAK activity (Hermand et al ., ; Devos et al ., ). In contrast, budding yeast Kin28 has no CAK activity (Cismowski et al ., ) and its activating T‐loop phosphorylation is mediated by the CDC28 cell cycle kinase‐activating kinase Cak1/Cvi1 (Kaldis et al ., ).…”
Section: Discussionmentioning
confidence: 97%